Early cow's milk consumption among Brazilian children: Results of a national survey - Gisele Ane Bortolini; Márcia Regina Vitolo; Muriel Bauermann Gubert; Leonor Maria Pacheco Santos (Brazilian Society of Pediatrics, 2013)
Objective: to assess the intake, frequency, and type of milk consumed by Brazilian children younger than 60 months of age. Methods: this was a cross-sectional study, which used secondary data from the National Demographic and Health Survey of 2006-2007. Data from 4,817 children under the age of 60 months were used. All analyses were performed with expanded samples. The dietetic survey assessed the previous day's consumption, and estimates were made through univariate analysis, presented as a percentage. Results: on the day prior to the survey, breast milk was consumed by 91% of the children younger than six months of age, by 61.5% of the children aged 6 to 12 months, and by 34.8% of the children aged 13 to 24 months. Among the children who had received other types of milk, cow's milk was consumed by 62.4% of the children younger than six months, by 74.6% of the children aged 6 to 12 months, and by approximately 80% of the children older than 12 months. Infant formulas were consumed by 23% of the children younger than six months of age, by 9.8% of the children aged 6 to 12 months, and by less than 1% of the older children. Soy milk consumption varied from 14.6% to 20% among the investigated ages. Non-breast milk consumption before the age of six months was more frequent in children living in the Northeastern and Southern regions. Conclusion: the results of the present study demonstrated that most children received cow's milk prematurely as a substitute for breast milk, highlighting the importance of the development of public policies to promote, protect, and support breastfeeding in all regions of Brazil, aiming at reversing the observed scenario.